Application of Problem Based Learning Through Identification of Arabic Grammatical Errors to Improve the Maharah of the Kitabah in Class VIII Kutub At-Turots Islami (KTI) MTs 2 Nurul Islam Mojokerto - Fahraini, Sovia; Rifa'i, Ahmad (Proceeding International Conference on Education, 2024)
Writing skills (maharah kitabah) in Arabic often face challenges in the form of repeated grammatical errors, especially at the secondary education level. To overcome this, this research examines the effectiveness of implementing the Problem Based Learning (PBL) model based on identifying grammatical errors in improving the writing skills of class VIII Kutub At-Turots Islami (KTI) students at MTs 2 Nurul Islam. This research uses a qualitative method with a descriptive approach. Data was collected through observation, interviews and document analysis, which focused on the learning process and improvement of students' writing skills after implementing PBL. Data analysis was carried out by reducing, presenting and drawing conclusions to understand the impact of applying the PBL method on students' writing abilities. The research results show that the PBL model based on grammatical error identification not only improves students' understanding of Arabic language structures, but also significantly improves their writing skills in terms of fluency, coherence, and grammatical accuracy. The application of this model has proven effective in encouraging students' active involvement and improving the quality of their writing.